PELAKSANAAN STRATEGI PROMOSI SEPEDA MOTOR MERK HONDA (DEALER SEPEDA MOTOR HONDA MENARA AGUNG PAYAKUMBUH SUMATERA BARAT) - Lestari, Agnes; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Menara Agung Payakumbuh a Hondamotorcycledealers who and sincethe end of2007 .Thesedealers not only sell themotorcycle , but alsothere is anofficial Hondaworkshopthat will serve every customerwho evermadea purchaseof motorcycles in theMenara AgungCabang Payakumbuh . To maintain the company afloat app opriate goals and achieve salestargets and business benef it , the Menara Agung Payaku uh implementing promotionalstrategies to achieve these goals . Research conducted at the Honda Dealers Menara AgungPayakumbuh aims to determine the promotion and impleme t ion of strategies that becomeinhibit ing factors and support in the implementat ion o promotional strategies in theMenaraAgung Cabang Payakumbuh . Data obtained in writing sci t if ic papers obtained bydistribut ing quest ionnaires to some consumers Menara A ung Cabang Payakumbuh selectedrespondents . Data analysis technique used is descript ve analysis techniques , whereafter thedata is collected , the data can be classif ied according to the indicators used in this study .Fromthe research that has been done , it is known tha the implementation of promotionalstrategies in theMenara Agung Cabang Payakumbuh can b categorized as "good enough ".It can be seen from the responses given by the respondents in the study . That is why it isrecommended that Menara Agung Cabang Payakumbuh over he Great Dealer implementpromotional strategies with better , and minimize obst cles that become obstacles in theimplementat ionof promotional strategies .Keyword : pemasaran, bauran pemasaran, promosi, strategi promosi.